2016
DOI: 10.1177/0363546516667906
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management After Outpatient Shoulder Arthroscopy: A Systematic Review of Randomized Controlled Trials

Abstract: On the basis of the evidence in this review, we recommend the use of ISBs as the most effective analgesic for outpatient arthroscopic shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 69 publications
(115 reference statements)
3
88
1
1
Order By: Relevance
“…2,3,12,13 A recent systematic review examining all modes of postoperative pain management following shoulder arthroscopy concluded that ISBPBs are superior to all other forms of postoperative pain control. 18 Existing studies examining ISBPBs are small and heterogeneous in terms of methodology, outcome measures, and therapeutic techniques/interventions, which creates difficulty in making comparisons. 2,9 Also, the majority of investigations have compared preoperative ISBPB with GA alone or with an ISBPB-GA combination.…”
Section: Résumémentioning
confidence: 99%
“…2,3,12,13 A recent systematic review examining all modes of postoperative pain management following shoulder arthroscopy concluded that ISBPBs are superior to all other forms of postoperative pain control. 18 Existing studies examining ISBPBs are small and heterogeneous in terms of methodology, outcome measures, and therapeutic techniques/interventions, which creates difficulty in making comparisons. 2,9 Also, the majority of investigations have compared preoperative ISBPB with GA alone or with an ISBPB-GA combination.…”
Section: Résumémentioning
confidence: 99%
“…Unplanned day of surgery admissions were significantly lower in the nerve block group, which is consistent with the trial data demonstrating improved early pain control and shorter postanesthesia care unit stays with nerve blocks. 13 However, this early benefit did not impact postdischarge outcomes, as emergency department visits and readmissions did not differ between groups. The reasons for emergency department visits may provide some insight into this finding.…”
Section: Discussionmentioning
confidence: 92%
“…11 Recent systematic reviews suggest that nerve blocks provide the highest degree of acute postoperative pain relief in ambulatory shoulder surgery patients; however, highquality evidence supporting a positive impact of regional anesthesia on longer-term outcomes is lacking. [12][13][14] Population-based studies could help to address this lack of data; however, available studies are at risk of bias as they have used exposures and outcomes that have not been…”
mentioning
confidence: 99%
“…However, ISBB is associated with serious complications . Thus, numerous alternative techniques have been investigated, but have been found to be nonequivalent analgesic methods when compared with ISBB . One new study showed that the US‐guided supraclavicular block, combined with a suprascapular block, was an effective alternative to the interscalene block for postoperative analgesia after shoulder instability surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Different analgesic methods, such as interscalene brachial plexus blocks (ISBBs), suprascapular blocks, and intra‐articular injections, have been performed to reduce shoulder pain and opioid‐related side effects, including emesis, itching, sleep disturbance, and constipation, after arthroscopic shoulder surgery. Most studies that have evaluated postoperative pain management after arthroscopic shoulder surgery have found that ISBB was superior to the other techniques . Therefore, ISBB has become a widely preferred technique as the sole anesthesia or an adjuvant to general anesthesia in shoulder surgeries .…”
Section: Introductionmentioning
confidence: 99%